2004
DOI: 10.1038/sj.bjc.6601621
|View full text |Cite
|
Sign up to set email alerts
|

Daily omega-3 fatty acid intake and depression in Japanese patients with newly diagnosed lung cancer

Abstract: The aim of the present study was to examine the association between daily omega-3 fatty acid intake and depression in Japanese cancer patients. Omega-3 fatty acid intake in 771 patients with newly diagnosed primary lung cancer was evaluated using a foodfrequency questionnaire, and the prevalence of depression was examined using the cutoff values for the depression subscale included in the Hospital Anxiety and Depression Scale. After adjustment for potential confounding factors, the odds ratio (OR) for depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 40 publications
2
55
1
Order By: Relevance
“…However, subjects with depression had significantly lower intake of ALA, which was a major dietary omega-3 FA (Suzuki et al, 2004). As ingested ALA can be converted into EPA and DHA in vivo, the result of our previous study (Suzuki et al, 2004) did not seem to be inconsistent with the studies indicating lower levels of EPA and DHA in phospholipids in depression (Edwards et al, 1998;Peet et al, 1998;Maes et al, 1999). Then, in the present study, we hypothesised that lower levels of EPA and DHA in serum phospholipids were associated with major depression and minor depression in lung cancer patients.…”
Section: Serum Fatty Acid and Depression In Cancer Patients M Kobayakmentioning
confidence: 97%
See 3 more Smart Citations
“…However, subjects with depression had significantly lower intake of ALA, which was a major dietary omega-3 FA (Suzuki et al, 2004). As ingested ALA can be converted into EPA and DHA in vivo, the result of our previous study (Suzuki et al, 2004) did not seem to be inconsistent with the studies indicating lower levels of EPA and DHA in phospholipids in depression (Edwards et al, 1998;Peet et al, 1998;Maes et al, 1999). Then, in the present study, we hypothesised that lower levels of EPA and DHA in serum phospholipids were associated with major depression and minor depression in lung cancer patients.…”
Section: Serum Fatty Acid and Depression In Cancer Patients M Kobayakmentioning
confidence: 97%
“…The present study was a three matched group case -control study, based in part on the Lung Cancer Database Project, which was a prospective cohort study for investigation of the pathogenesis of and development of new therapy for lung cancer at the National Cancer Center Hospital East and the National Cancer Center Research Institute East, Japan (Suzuki et al, 2004). The project, including the present study, was approved by the Institutional Review Board and the Ethics Committee of the National Cancer Center, Japan.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In seven of the studies that found associations, the relationship between n-3PUFA intake and depression was found following adjustment for confounders (41 -43,46 -48,51) . In three of these studies, however, associations were reduced following adjustment for confounders (43,46,51) , and in one study no association between n-3PUFA intake and depressed mood remained following adjustment for the confounders, age and deprivation (50) .…”
Section: Epidemiological Evidencementioning
confidence: 99%